The ‐2518 A/G MCP‐1 and ‐403 G/A RANTES promoter gene polymorphisms are associated with psoriasis vulgaris. (19th October 2016) - Zablotna, M.; Sobjanek, M.; Purzycka‐Bohdan, D.; Szczerkowska‐Dobosz, A.; Nedoszytko, B.; Nowicki, R.
Summary: Background: Polymorphic variants of the genes encoding monocyte chemoattractant protein‐1 (MCP‐1/CCL2) and regulated upon activation normal T‐cell expressed and secreted (RANTES/CCL5) and their protein serum levels have not been widely explored in psoriasis. Aim: To clarify the effect of the MCP‐1 (‐2518 A/G) and RANTES (‐403 G/A) promoter gene polymorphisms on the risk and clinical manifestation of psoriasis. Methods: We enrolled 160 unrelated patients with psoriasis vulgaris and 160 healthy, unrelated, age‐ and sex‐matched volunteers. The promoter gene polymorphisms were analysed using amplification refractory mutation system (ARMS)‐PCR and single specific primer (SSP)‐PCR. Serum levels of cytokines were measured using ELISA. Results: The presence of the MCP‐1–2518 GG genotype was statistically more frequent in patients and it was associated with an increased risk of psoriasis (OR = 1.94; P = 0.04). In patients with late‐onset (≥ 40 years) psoriasis, the presence of the RANTES ‐403 AA genotype was statistically more frequent (OR = 3.65; P < 0.01) while ‐403 GG was less frequent (OR = 0.44; P < 0.01). Moreover, the A allele (AA or AG) in the ‐403 RANTES polymorphism was associated with an increased risk of developing severe psoriasis (OR = 2.02; P = 0.03). Serum levels of both chemokines were elevated. RANTES serum concentration was significantly higher in patients with Psoriasis Area and Severity Index > 15. Conclusions: The results of our analysis suggest that the ‐2518 A/G MCP‐1 and ‐403 G/A RANTES promoter gene polymorphisms may be risk factors for psoriasis and may influence its clinical presentation.